The Relationship among Indonesian Women Self-Esteem with Breast Cancer Beliefs Screening: Attitude, Knowledge, and Barriers to Mammographic (European Journal of Behavioral Sciences, 2020)
Breast cancer is one of the prevalent non-communicable diseases in developed and under-developed countries, especially Indonesia. It’s necessary to promote and aware breast cancer screening practices for early detection of breast cancer. This study aims to analyze relationship between self-esteem and breast cancer beliefs screening among Indonesian women. This study was conducted with a quantitative approach and performed in Indonesia. Participants of this study were 209 women. Measurement of self-esteem was done by using Rosenberg’s Self-Esteem Scale by Rosenberg, and breast cancer beliefs screening was measured using adaptation of Breast Cancer Screening Beliefs Questionnaire by Kwok, et al. The Results of data analysis showed that self-esteem has positive correlation with knowledge (r = .131, p = .029) and negative correlation with barriers to mammographic screening (r = -.128, p = .039) but, there is no correlation with attitude (r = .091, p = .096). From the results, it can be concluded that Indonesian women with high self-esteem has more knowledge and has little barriers to mammographic screening.